2018
DOI: 10.12659/msm.909661
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Report Requiring Continuation of Research to Confirm Fallopian Tube Adenocarcinoma: A Non-Experimental, Non-Randomized, Cross-Sectional Study

Abstract: BackgroundTransvaginal ultrasound has fair characteristics, and pathology is an invasive technique for fallopian tube tumor diagnosis. Magnetic resonance images have better intra- and inter-observer reliabilities for detection of primary fallopian tube malignant tumor(s) than the other diagnostic modalities. The purpose of this study was to investigate parameters of different types of magnetic resonance images for women with fallopian tube adenocarcinoma and to compare these parameters with the FIGO grading sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…A previous study showed that apparent diffusion coefficient values were significantly higher in women with FIGO grade 1 than in women with FIGO grade 3 (p < 0.0001, q = 16.591), and the Spearman correlation coefficient was 0.1012 between the mean apparent diffusion coefficient and FIGO grading. 9 However, in our case, the uterine lesion was ignored by physicians in the initial diagnosis because it was small, and it was only observed in one slice of tomographic images. According to the FIGO guideline, if there are uterine or ovarian metastases, the staging will change.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A previous study showed that apparent diffusion coefficient values were significantly higher in women with FIGO grade 1 than in women with FIGO grade 3 (p < 0.0001, q = 16.591), and the Spearman correlation coefficient was 0.1012 between the mean apparent diffusion coefficient and FIGO grading. 9 However, in our case, the uterine lesion was ignored by physicians in the initial diagnosis because it was small, and it was only observed in one slice of tomographic images. According to the FIGO guideline, if there are uterine or ovarian metastases, the staging will change.…”
Section: Discussionmentioning
confidence: 78%
“…Several previous studies 9 , 10 have described the MRI findings of PFTC as a sausage-shaped adnexal mass or a multilocular cystic mass with a cog-and-wheel appearance, and the solid portion shows high intensity on diffusion-weighted images. There has even been a suggestion to include MRI in the International Federation of Gynecology and Obstetrics (FIGO) guideline for grading of malignancies in the female genital tract.…”
Section: Discussionmentioning
confidence: 99%
“…Literature data suggest that magnetic resonance imaging (MRI) and positron emission tomography (PET) are often used for PFTC diagnostics [1,22,23]. According to some authors these methods not only visualize a tumor and its structure, but unlike USS, allow to recognize fine details of contrast, of hydrophilic and chemical specifics of tissues, to identify tumor infiltrates, their borders and metastases in regional lymph nodes [23][24][25]. There are even suggestions to include MRI into FIGO guidelines as a compulsory diagnostic procedure for PFTC [24].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to sonography, MRI, in addition to anatomical features, allows recognition of fine details of contrast, hydrophilicity, and chemical features of the tumor and detection of metastases in the lymph nodes. Some authors consider it necessary to include in FIGO clinical protocols as a mandatory method of examination when FTC is suspected [31].…”
Section: Problems and Capabilities Of Ftc Diagnosismentioning
confidence: 99%